Australian migrants' social cultural adaptation and consumption behaviour towards food and alcohol. (28th November 2018) - Arli, Denni; Kim, Jeawon; Rundle‐Thiele, Sharyn; Tkaczynski, Aaron
Abstract: Australia is one of the most successful multicultural countries in the world due to successive waves of migration from Europe and recently Asia. Nonetheless, new migrants coming to Australia are not always able to adapt to Australian culture due to language and cultural barriers. Hence, the purpose of this study is to segment migrants based on their cultural adaptation and subsequently to examine similarities and differences between those segments in regards to their health‐related behaviour (i.e., alcohol and food consumption). A cross‐sectional study of migrants in Australia ( N  = 408) suggests that migrants from Asia have the greatest difficulty in adapting to the local culture due to language barriers. This study will assist public policy makers and social marketers in creating effective campaigns and interventions to reduce excessive alcohol consumption and obesity among migrants.